Oxidation Kinetics of Soot on Acicular Mullite Membrane Filter Using Electron Microscopy and Thermogravimetric Analysis - Saenkhumvong, Eakkawut; Karin, Preechar; Charoenphonphanich, Chinda; Vittayakorn, Naratip; Hanamura, Katsunori (My University, 2020)
This paper investigates the oxidation kinetics of carbon black on acicular mullite using thermogravimetric (TGA) and mullite microstructures by scanning electron microscopy (SEM) for the development of diesel particulate filters (DPFs). It is observed that the amount of each chemical composition strongly affects the structure of mullite. The addition of AlF3 and V2O5 to mullite promotes the growth of needle-shaped mullite crystals. Thermogravimetric analysis was used to investigate and characterize chemical kinetics of soot oxidation for better understanding of designs and configurations of diesel particulate filters. The mass conversion of soot on the acicular mullite (ACM) is oxidized faster than that on the mullite (ML) membrane at all temperatures examined. The calculation of apparent activation energy (Ea) of soot oxidation with isothermal methods on mullite was presented. The results showed that activation energy of soot oxidation is enhanced with ACM than with ML at all temperatures examined. The average calculated apparent activation energy of soot oxidation on ACM and ML are 146.4 kJ/mole and 155.3 kJ/mole, respectively.
Keywords: Acicular mullite; Microstructure; Morphology; Particulate filter; Soot oxidation kinetic